Socio-economic factors determine maternal and noenatal outcomes in women with peripartum cardiomyopathy: a study of the ESC EORP PPCM registry. (3rd October 2022) - Sliwa-Hahnle, K; Van Der Meer, P; Viljoen, C; Jackson, A M; Petrie, M C; Maggioni, A P; Laroche, C; Regitz-Zagrosek, V; Tavazzi, L; Roos-Hesselink, J W; Seferovic, P; Frogoudaki, A; et al.
Abstract: Background: Peripartum cardiomyopathy (PPCM) is a global disease associated with substantial morbidity and mortality. Purpose: The aim of this study was to analyse to what extent country- and individual-level socioeconomic factors were associated with maternal and neonatal outcomes. Methods: In 2011, >100 national and affiliated member cardiac societies of the European Society of Cardiology (ESC) were contacted to contribute to a global registry on PPCM, under the auspices of the ESC EORP Programme. Country-level sociodemographic factors were Gini coefficient (GINI), health expenditure (HE) and human developmental index (HDI). Individual-level sociodemographic factors were income and educational attainment. We investigated the characteristics and outcomes of women with PPCM and their babies according to individual and country-specific socioeconomic status. Results: 739 women from 49 countries were enrolled (Europe [33%], Africa [29%], Asia-Pacific [15%], Middle East [22%]). Overall, 142 (19%) of women were from countries with low HDI, 307 (42%) medium HDI and 290 (39%) high HDI. Patients of Black African ethnicity were almost all from low HDI countries (99.3%), Middle Eastern and Asian patients from medium HDI (37.7% and 26.2%), and Caucasian patients were mostly from high HDI (72%, p<0.001). Women from countries with low HDI had lower income and educational attainment. They also underwent fewer Caesarian sections, but breastfed for longer (20 versus 6 months, p<0.001). Low HDI and low GINI were associated with greater LV dilatation at time of diagnosis (p<0.001), but LV ejection fraction (LVEF) did not differ according to HDI, HE or GINI. Countries with low HE prescribed guideline-directed heart failure therapy less frequently. Low HE was associated with more frequent mortality (p<0.002), whereas HDI and GINI were not. Women from countries with low HDI and low HE had significantly less recovery of LV function. Analysis of maternal outcome as per highest level of educational attainment (i.e., primary [n=154], secondary [n=342], tertiary [n=126]), showed significant differences in LVEF at 6 months (43.7+12.9, 46.5+13.0 and 48.9+11.7 respectively, p=0.022). Low maternal income, irrespective of region of origin, was independently associated with poor outcome (composite of maternal death, re-hospitalization, or LV non-recovery). Neonatal death was more prevalent in countries with low HE (p=0.009) and low HDI (p=0.023) but was not influenced by maternal sociodemographic parameters. Conclusion: Maternal and neonatal outcomes depended on country-specific socioeconomic characteristics, with a greater prevalence of maternal and neonatal deaths in women from countries with low HE. Globally, women with low income and lower levels of educational attainment had poorer outcomes, irrespective of region. Attempts should be made to improve patient education, and allocation of adequate health resources to improve maternal and neonatal outcomes in PPCM. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): 1. EurObservational Research Programme in conjunction with the Heart Failure Association of the European Society of Cardiology Study Group on Peripartum Cardiomyopathy2. Cape Heart Institute, University of Cape Town, Cape Town, South Africa